Nauka i sztuka. Wokół konserwatorskich prac nad płaskorzeźbą Stanisława Wyspiańskiego pt. „Macierzyństwo" wykonaną w plastelinie - Płuska, Ireneusz (Przestrzenie Teorii, 2009)
The problem undertaken in this article concerns a complicated, but also an extremely interesting both for science and the art of conservation of the repair of a bas-relief of a sculpture Macierzyństwo [Motherhood] executed in plasticine by Stanisław Wyspiański in 1902. Due to the untypical material which was used to make this relief, there are no practical examples of conservation and references in literature, this conservation work should be treated as a certain kind of experiment in art conservation which belongs to the realm of art, but which is also carried out based on scientific methods. During conservation work on this relief particularly protected were numerous fingerprints of Wyspiański himself which he had left on the sculpture. These carriers of historical memory of the great master, invest the masterpiece with a specific character of the texture of a bas-relief and offer a closer contact of the viewer with the deceased artist and his work of art.